USING STORYTELLING TO ENHANCE LANGUAGE LEARNING - Rustamova, Sevinch (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
This article explores how storytelling can serve as an effective strategy in language learning. It examines how narratives—both traditional and digital—help learners improve vocabulary, speaking, listening comprehension, and motivation.